The Use of ESA Technique on Reading Comprehension at MtsN Ganting Padang Panjang - Fidrian, Nanda; Lismay, Leli (FOSTER: Journal of English Language Teaching, 2021)
The researcher aimed to conduct this research due particular in students reading comprehension at Mts N Ganting Padang Panjang. The researcher found the problems that first, students interest in reading a text was still lacking. Second, students still have difficulty in reading comprehension. Third, students had a lack of vocabularies in translating the meaning of the word. Therefore, this research is to know how the teacher applies the ESA technique on reading comprehension. The research aimed to analyze teacher apply ESA technique on reading comprehension. This research used a descriptive qualitative research design. The object of this research were two English teachers in Mts N Ganting Padang Panjang. The instruments of this research were questionnaire and interview. The result of the research showed that ESA technique is suitable and effective for reading comprehension that can be seen from teacher apply ESA technique on reading comprehension. Engage, in this elements the teacher motivate students and active their background knowledge. The study, in this elements teacher, focus on the topic in the text and guide students in understanding the content of the text. Activate, in this elements teacher gives exercises and assignment to students, then concludes the contents of the text that has been learned.